2009
DOI: 10.1111/j.1440-1843.2009.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Boost of mucosal secretory immunoglobulin A response by clarithromycin in paediatric influenza

Abstract: Background and objective:The antiviral neuraminidase inhibitor oseltamivir (OSV) is used to treat influenza. The macrolide clarithromycin (CAM) is used to treat bacterial infections and has anti-inflammatory and immunomodulatory activities. This retrospective study investigated the immunomodulatory effects of CAM in children presenting with influenza A. Methods: The study recruited 40 children with acute influenza, and grouped them according to the treatment received: 5-day treatment with OSV (n = 14), CAM (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 25 publications
3
43
0
1
Order By: Relevance
“…These experiments were done because they had the unexpected finding that patients with paediatric influenza who were treated orally with oseltamivir for 5 days had significantly low levels (about 60% reduction on day five) of anti-influenza secretory-immunoglobulin A nasopharyngeal fluids compared with levels in patients who were not treated with oseltamivir. 134 Their findings are consistent with our findings that serum haemagglutinin inhibition antibody response was decreased by oseltamivir administration, although secretory immunoglobulin G antibody could not be analysed in our study because the data were not reported in the CSRs. 133,134 These findings are also consistent with the evidence on the mode of action of oseltamivir from animal models 8,58,135 and from viral challenge, randomised, placebo-controlled studies in humans.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These experiments were done because they had the unexpected finding that patients with paediatric influenza who were treated orally with oseltamivir for 5 days had significantly low levels (about 60% reduction on day five) of anti-influenza secretory-immunoglobulin A nasopharyngeal fluids compared with levels in patients who were not treated with oseltamivir. 134 Their findings are consistent with our findings that serum haemagglutinin inhibition antibody response was decreased by oseltamivir administration, although secretory immunoglobulin G antibody could not be analysed in our study because the data were not reported in the CSRs. 133,134 These findings are also consistent with the evidence on the mode of action of oseltamivir from animal models 8,58,135 and from viral challenge, randomised, placebo-controlled studies in humans.…”
supporting
confidence: 93%
“…134 Their findings are consistent with our findings that serum haemagglutinin inhibition antibody response was decreased by oseltamivir administration, although secretory immunoglobulin G antibody could not be analysed in our study because the data were not reported in the CSRs. 133,134 These findings are also consistent with the evidence on the mode of action of oseltamivir from animal models 8,58,135 and from viral challenge, randomised, placebo-controlled studies in humans. 27 Pro-inflammatory cytokines, including interleukin 6, tumour necrosis factor alpha and interferon gamma, were completely suppressed by oseltamivir administered 28 hours after the experimental inoculation of influenza virus, whereas the reduction of viral titre in nasal lavages was partial.…”
supporting
confidence: 93%
“…As such, a recent Cochrane review found minimal evidence in support of the use of macrolides in infants with bronchiolitis [109]. Finally, SAWABUCHI et al [110] have recently shown that the addition of clarithromycin to oseltamivir augmented secretory (s)IgA production and restored local mucosal sIgA levels in children with acute influenza, suggesting a boosting effect on the nasopharyngeal mucosal immune response in children with influenza A.…”
Section: Respiratory Viral Infectionsmentioning
confidence: 99%
“…In this regard, we have previously reported that administration of CAM in influenza A virus (IAV)-infected mice resulted in suppression of tumor necrosis factor alpha and augmentation of interleukin-12 production in the blood, resulting in alleviation of the flu symptoms (18), while oral treatment with OSV attenuated the induction of respiratory anti-IAV specific secretory IgA (S-IgA) immune responses (39). Furthermore, we have recently verified in IAV-infected children that oral CAM augmented the nasopharyngeal mucosal immune responses, while OSV suppressed the production of mucosal anti-IAV S-IgA (37). Of interest, we have also reported that 75% of patients treated with the combination of CAM and OSV showed increases in S-IgA production to levels similar to those seen in patients treated with CAM alone (37).…”
mentioning
confidence: 94%
“…Furthermore, we have recently verified in IAV-infected children that oral CAM augmented the nasopharyngeal mucosal immune responses, while OSV suppressed the production of mucosal anti-IAV S-IgA (37). Of interest, we have also reported that 75% of patients treated with the combination of CAM and OSV showed increases in S-IgA production to levels similar to those seen in patients treated with CAM alone (37). Others have also reported that CAM acted on the viral replication cycles, resulting in inhibition of progeny virus production in vitro (25,26), and modulated airway inflammation in IAV infection by reduction of the viral receptor, sialic acid with an ␣2,6 linkage on the airway epithelial cells, through inhibition of nuclear factor kappa B (NF-B) expression and increase in intraendosomal pH (45).…”
mentioning
confidence: 99%